The Influence of Texture Depth on Low-Speed Skidding Resistance of Pavement at Difficult Site Areas - Ron Aldrino Chan @ Ron, Buking (Universiti Malaysia Sarawak (UNIMAS), 2005)
Accident on wet and slippery road has always been a problem especially for road engineer as they try to find ways to improve and develop an economical and non slippery road surfaces for the safety of the road users. Skidding on wet pavement has been identified as one of the factors that contributed to this accident rate. Skidding also happens most frequently when pavement surface does not provide adequate friction. This project presents the results and the evaluation of the influence of texture depth on skid resistance especially on difficult site areas in Kuching city, which are roundabouts and traffic junctions. The data obtained was analyzed to identify the significant relationships between texture depth values and skid resistance values as measured by the British Pendulum Tester and Sand Patch Method. Based on the test conducted at six selected difficulty site areas, it has indicates that there is a significant correlation between texture depth values and skid resistance values, which the higher the texture depth, the lower the skid resistance. Also the skid resistance values are highly dependent on the texture depth of pavement surface.